Recovery of uranium from Philippine wet phosphoric acid using D2EHPA-TOPO solvent extraction - Palattao, Botvinnik L.; Diwa, Reymar R.; Intoy, Socorro P.; Vargas, Edmundo P.; Marcelo, Editha A.; Tabora, Estrellita U.; Ramirez , Jennyvi D.; Reyes, Rolando Y. (2018)
Recovery of uranium from Philippine wet phosphoric acid was studied using a synergistic mixture of 0.5 M D2EHPA - 0.125 M TOPO diluted in kerosene. Results from characterization of materials in phosphate processing revealed the presence of valuable elements such as uranium and rare earths in both raw materials and fertilizer products. Variation of operating parameters on extraction such as P2O5 content and optical density was found to be inversely proportional with the extraction efficiency. The reaction was found to establish rapid equilibrium and is exothermic in nature. Distribution coefficient for the extraction of uranium from 27% P2O5 phosphoric acid was determined to be at 10.71 at about 25Â°C. Analysis of the equilibrium data and McCabe-Thiele plot based on batch testing indicates a 92.59% recovery rate could be achieved in three-ideal extraction stages at an aqueous to organic phase volume ratio of 4:1.